Peran E-Wallet Dalam Mendorong Perilaku Konsumsi Generasi Milenial - Linus, Marvin (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The development of financial technology, particularly e-wallets, has transformed consumption behavior, especially among millennials. This study aims to analyze the role of e-wallets in driving consumption behavior among Indonesian millennials. A quantitative survey method was employed, with questionnaires distributed to 200 millennial respondents who are active e-wallet users. Data were analyzed using descriptive statistics and multiple linear regression to examine the relationship between e-wallet usage and consumption behavior. The results indicate that e-wallet usage has a positive and significant effect on increasing consumption frequency and impulsive buying behavior among millennials. Transaction security and incentives such as cashback were identified as key factors supporting e-wallet adoption. However, the convenience of digital payments also poses risks of excessive consumption that require attention. This study offers recommendations for e-wallet service providers and policymakers to enhance digital financial literacy programs to promote healthy and sustainable consumption behaviors in the era of financial technology.